10.61991 THE INFLUENCE OF THE INTERNET OF THINGS IN EDUCATION: META-ANALYSIS - Abdullah Ardi; Agus Triyono; Sutarto; Rusmawan; Tomi Apra Santosa (AKADEMI TEKNIK ADI KARYA, 2023)
This research aims to determine the influence of the Internet of Things (IoT) in education. This type of research is meta-analysis research. The research sample came from an analysis of 13 national and international journals. Search research data through google Scholar, ERIC, ScienceDirect, and ProQuest databases. Data search keywords are Internet of Things and Internet of Things in Education. The inclusion criteria in the meta-analysis are publications in 2020-2023, research related to the internet of things in education, publications from indexed journals SINTA, Scopus, and WOS, and research reporting complete data to calculate effect size values. Analysis uses quantitative analysis by calculating the value of effect size with the help of Comperehensive meta-analysis (CMA) applications. The results concluded that the average value of effect size was 0. 95 with high ketogeri effect size. These findings explain the significant influence of the Internet of things in education.